2015
DOI: 10.1645/14-584.1
|View full text |Cite
|
Sign up to set email alerts
|

Host Specificity of a Parasitic Fluke: IsPosthodiplostomum minimuma Centrarchid-Infecting Generalist or Specialist?

Abstract: Parasite host specificity has important implications for species diversity estimates, food web dynamics, and host shifts. "White grub" is the metacercaria stage of a fluke ( Posthodiplostomum minimum ) that occurs in many fish species, but no attempt has been made to quantify variation in host use by this worm. Here we used 2 approaches to evaluate host specificity within the strain that infects centrarchids ( P. minimum centrarchi). First, we measured parasite loads in 2 centrarchid hosts, bluegill ( Lepomis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 43 publications
2
24
1
1
Order By: Relevance
“…On the contrary, others can be found in many host species, which are considered as generalists [ 14 16 ]. Parasite-sharing usually depends on the similarity of physiological characteristics among host species, which is likely to be higher in hosts that are closely related phylogenetically and/or share similar feeding habits, ecological niches, or geographic locations [ 14 , 17 21 ]. According to Rohde [ 22 ], a method to estimate parasite host specificity consists of the evaluation of “the number of host species from which the parasite has been collected.” Other methods comprise the estimation of the variation in parasite infection levels among host species and the analysis of phylogenetic distinctiveness of hosts [ 13 , 14 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, others can be found in many host species, which are considered as generalists [ 14 16 ]. Parasite-sharing usually depends on the similarity of physiological characteristics among host species, which is likely to be higher in hosts that are closely related phylogenetically and/or share similar feeding habits, ecological niches, or geographic locations [ 14 , 17 21 ]. According to Rohde [ 22 ], a method to estimate parasite host specificity consists of the evaluation of “the number of host species from which the parasite has been collected.” Other methods comprise the estimation of the variation in parasite infection levels among host species and the analysis of phylogenetic distinctiveness of hosts [ 13 , 14 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…3 and 4) to infer host-specificity within Centrarchidae (Locke et al 2010). Based on infections in bluegill ( Lepomis macrochirus ) vs white crappie ( Pomoxis annularis ) and literature reviews, Lane et al (2015) suggested that P. minimum is more of a host specialist than previously recognized and that P. m. centrarchi is a Lepomis specialist lacking host preferences outside of the genus. Given the molecular evidence for multiple Posthodiplostomum ‘minimum’ species within centrarchids, we refer to metacercariae in this study as Posthodiplostomum and identify specific species when appropriate.…”
Section: Introductionmentioning
confidence: 99%
“…A fundamental question regarding host specificity is the extent to which a putative generalist parasite performs equally well in all exploited host species, namely, whether these hosts are all equally compatible for the parasite [ 4 ]. This question has important implications, not only for understanding the evolution of specificity, but also for population dynamics and epidemiology of generalist parasites [ 5 ].…”
Section: Introductionmentioning
confidence: 99%